INFLUENCE OF SOCIAL AND EMOTIONAL LEARNING AND LANGUAGE DEVELOPMENT ON KINDERGARTEN TEACHERS’ PERFORMANCE - Hayag, Minigilda C; Collantes, Leila M; Pentang, Jupeth (LPPM Universitas Jambi, 2025)
The benefits of social and emotional learning in early childhood education have been underlined by research more and more as a critical component in influencing teachers’ methods and encouraging successful student outcomes. Thus, this study explored the kindergarten teachers’ social and emotional learning practices, strategies for teaching language development, and their relationship to teaching performance. It utilized an embedded mixed-method research design with 108 kindergarten teachers sampled from 36 schools in a selected Philippine region. Data were gathered online with a Social-Emotional Competence Questionnaire and a Teacher Survey Instructional Orientation Questionnaire. Results indicated that high teaching performance was associated with experience and position. Effective language development and SEL practices, particularly those related to social awareness, supported cognitive and emotional growth. This study found that effective language development and SEL practices also strengthened the outcome of teaching and learning. Combining language development techniques with social and emotional learning is vital to promote teacher effectiveness and the overall development of young children.